Theoretical and empirical contributions to structural change and integral human development in Latin American economies - Malvicino, Facundo Ezequiel (2024)
Fil: Malvicino, Facundo Ezequiel. Universidad Nacional de Río Negro. Centro Interdisciplinario de Estudios en Economía, Territorio y Sociedad. Río Negro, Argentina.